Supporting First Grade Students Learning Number Facts Up To 10 Using A Parrot Game - Putra, Zetra Hainul; Darmawijoyo, Darmawijoyo; Hertog, Jaap den; Ilma, Ratu (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2011)
Knowing number facts up to 10 become crucial if we want students toÃ‚Â solve addition and subtraction problems Ã‚Â using more abbreviatedÃ‚Â strategies. Otherwise, students will keep counting one-by-one until theyÃ‚Â get an answer. One of important number facts is number pairs thatÃ‚Â make ten because it is an important Ã¢â‚¬ËœbenchmarkÃ¢â‚¬â„¢ that students will referÃ‚Â to constantly. Considering the important of number facts up to 10, weÃ‚Â designed a parrot game activity to supports students learning process.Ã‚Â We designed an instructional activity based on Realistic MathematicsÃ‚Â Education (RME) approach. We tried this instructional activity withÃ‚Â twenty seven first grade students in SDN 179 Palembang. As a result,Ã‚Â we found that many first grade students were able to know numberÃ‚Â facts up to 10, but they still need models to support their thinking.Keywords: number facts up to 10, number pairs that make 10, andÃ‚Â parrot game.Ã‚Â DOI: http://dx.doi.org/10.22342/jme.2.2.776.163-172